Analisis Kelayakan Finansial Pabrik Penggilingan Beras Organik “BOTANIK” (Studi Kasus Unit Processing Padi Organik Tani Mandiri I di Desa Lombok Kulon Kecamatan Wonosari Kabupaten Bondowoso) - Iftitah Hevi Riyanti; Jabal Tarik Ibrahim; Istis Baroh (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2018)
Organic rise is a rice which produce organically from paddy without using fertilizer and chemical perticides. The market demand on organic rice has increased drastically and effected on promising market prospect. Lombok Kulon village is one of the area di Bondowoso district has been applied organic farming on organic rice. Tani mandiri 1 is one of farmer group who are cultivating organic rice with the certificate. The subject of research was taken at Lombok Kulon village, Wonosari regency, Bondowoso district. The method of research was descriptive qualitative with purposive sampling. The objectives of the research are: (1) to analyze the financial structure; (2) To know the criteria of financial feasibility. The quantitave analysis is purposed to analyze the aspects of financial which are cash flow, NPV (Net Present Value), IRR  (Internal Rate of Return), Net B/C Ratio, Payback Period and sensitivity analysis financial. The research showed that Unit Processing Padi Organik Tani Mandiri I was a viable unit based on the result of financial analysis. It was proved by NPV score which was Rp. 1.456.180.006 with 6 % of discount rate, the score of Net B/C Ratio was 1,65 or more than (>) 1, and IRR score was 23,80% or more than (>) 6% of bank interest rate.Organic rise is a rice which produce organically from paddy without using fertilizer and chemical perticides. The market demand on organic rice has increased drastically and effected on promising market prospect. Lombok Kulon village is one of the area di Bondowoso district has been applied organic farming on organic rice. Tani mandiri 1 is one of farmer group who are cultivating organic rice with the certificate. The subject of research was taken at Lombok Kulon village, Wonosari regency, Bondowoso district. The method of research was descriptive qualitative with purposive sampling. The objectives of the research are: (1) to analyze the financial structure; (2) To know the criteria of financial feasibility. The quantitave analysis is purposed to analyze the aspects of financial which are cash flow, NPV (Net Present Value), IRR  (Internal Rate of Return), Net B/C Ratio, Payback Period and sensitivity analysis financial. The research showed that Unit Processing Padi Organik Tani Mandiri I was a viable unit based on the result of financial analysis. It was proved by NPV score which was Rp. 1.456.180.006 with 6 % of discount rate, the score of Net B/C Ratio was 1,65 or more than (>) 1, and IRR score was 23,80% or more than (>) 6% of bank interest rate.